Treatment of visual neglect in elderly patients with stroke: a single-subject series using either a scanning and cueing strategy or a left-limb activation strategy. - Bailey, M; Riddoch, M; Crome, P (2002)
BACKGROUND AND PURPOSE: The presence of unilateral visual neglect (UVN) may adversely affect functional recovery, and rehabilitation strategies that are practical for use in clinical settings are needed. The purpose of this study was to evaluate the use of 2 approaches to reduce UVN in people who have had strokes. SUBJECTS: Seven elderly patients with stroke and severe left UVN, aged 60 to 85 years, were recruited from a stroke rehabilitation unit. METHODS: A nonconcurrent, multiple-baselines-across-subjects approach, with an A-B-A treatment-withdrawal single-subject experimental design, was used. Five subjects received a scanning and cueing approach, and 2 subjects received a contralesional limb activation approach, for 10 one-hour sessions. In the former approach, active scanning to the left was encouraged by the therapist, using visual and verbal cues and a mental imagery technique, during reading and copying tasks and simple board games. In the latter approach, functional and goal-oriented left upper-limb activities in neglected hemispace were encouraged. Unilateral visual neglect was examined by a masked (blinded) examiner throughout all phases using the Star Cancellation Test, the Line Bisection Test, and the Baking Tray Task. Data were analyzed using visual and inferential statistical techniques. RESULTS: Both subjects who received limb activation and 3 of the 5 subjects who received scanning and cueing showed a reduction in UVN in one or more tests. This improvement was maintained during the withdrawal phase. DISCUSSION AND CONCLUSION: Both approaches had a positive effect of reducing aspects of UVN in some subjects relative to no-treatment baselines. However, causality cannot be assured in the absence of controls. The approaches are practical for use in rehabilitation settings. These procedures warrant further replication across subjects, settings, and therapists.